An evidence-based case for quality online initial teacher education - Pelliccione, Lina; Morey, Valerie; Walker, Rebecca; Morrison, Chad (AUSTRALASIAN SOC COMPUTERS LEARNING TERTIARY EDUCATION-ASCILITE, 2019)
The rapid expansion of fully online delivery of initial teacher education (ITE) seen in the past decade has generated some concerns about impact on teacher quality. This is set within broader, sustained concerns about ITE generally. Much of the criticism of online ITE has been made without sufficient evidence to support the claims, largely due to the still-nascent evidence base. The data presented here contributes to that evidence base by providing demographic and academic achievement insights for cohorts of graduate teachers (N = 2008) across the years 2012 to 2018 who have engaged in fully online ITE at an Australian university. The literature has recognised the traditional barriers to accessing higher education for many of these students, including women, the mature-aged, and those with family and work responsibilities. Performance data for online ITE students within their programs demonstrates that they are breaking through these barriers associated with the digital divide. Analysis of who these people are, where they come from, and how they are performing provides valuable insights into online ITE, at a time when the value of broadening access to education and digital equity are being widely acknowledged. Implications for practice or policy:•The educational community should consider the achievement of online ITE students and contributions they can make to education and schools.•The educational community should consider the contributions online ITE can make to broadening access to higher education and digital equity.